The Effect of Folic Acid on Learning and Spa-tial Memory in Electrical Leisions Model of Nu-cleus Basalis Magnocellularis: Animal Model of Alzheimer’s Disease - Nastaran Zamani (Iranian South Medical Journal)
Background: Alzheimer's disease (AD) is a neurodegenerative disorder with severe cognitive impairments. Taking into account the role of folic acid on improving cognitive functions in some disease models, the present study aimed to examine the effect of folic acid on spatial learning and memory impairment induced by bilateral electrical lesion of nucleus basalis magnocellularis (NBM) in Alzheimer’s disease model of adult male rats. Materials and Methods: In this experimental study, 49 adult male Wistar rats were randomly divided into seven groups: Negative control, NBM lesion (bilateral electric lesion of NBM), sham lesion (electrode entry into NBM without induction of electric current), vehicle (lesion+saline), and lesion+folic acid (FA 5, 10, 15 mg/kg). In the treated groups, intraperitoneal injection of folic acid or saline was performed for one week, 30 minutes after the NBM lesion. Then, they were trained for five days by Y-shaped maze. Twenty-five days after the training, a memory recall test was performed to evaluate long-term memory. Results: NBM bilateral lesion decreased learning and spatial memory compared to the negative and sham control groups (P˂0.001). There was a significant increase in learning and spatial memory in the lesion+FA 10 mg/kg (p<0.05) and lesion+FA 15 mg/kg (P<0.01) groups compared to the lesion group. Conclusion: The results of this study show that folic acid improves learning and spatial memory in Alzheimer's disease models with bilateral electrical lesions of NBM in adult male rats.